Macular hole surgery in patients with end-stage choroideremia - Zinkernagel, MS; Groppe, M; MacLaren, R (2013)
Objective: To assess macular hole surgery in patients with end-stage choroideremia with regard to anatomic closure and visual outcome. Design: Retrospective, interventional case series. Participants: Thirty adult male patients with a diagnosis of advanced choroideremia were reviewed and underwent spectral domain optical coherence tomography (OCT) as part of the screening process for a gene therapy clinical trial. From within that cohort, 3 were identified as having a full-thickness macular hole (FTMH). Methods: A 23-gauge pars plana vitrectomy was performed with peeling of the inner limiting membrane and gas tamponade. Preoperative best-corrected visual acuity ranged from perception of light to 6/24. Main Outcome Measures: Prevalence of FTMH in advanced choroideremia, morphologic phenotype characteristics of FTMH in OCT, pre- and postoperative best-corrected visual acuity, and closure rate after surgery. Results: The prevalence of FTMH in advanced choroideremia in our cohort was 10%. One hole was associated with significant macular schisis, presumed to be attributable to degeneration of outer retinal layers. Anatomic closure was achieved in all 3 patients and confirmed with spectral domain OCT. Gas tamponade lasted approximately twice as long as might be expected compared with standard FTMH surgery. Objective visual acuity did not improve; however, perceived vision improved in all patients. Conclusions: Although FTMH in choroideremia is a rare finding, it could potentially mask central progression of the disease. Regular screening may help to diagnose holes at an earlier stage when the visual prognosis after surgery may be better. Standard macular hole surgery seems to be effective in gaining anatomic closure, which would be significant for patients who subsequently require macula detachment for subretinal gene therapy. © 2013 by the American Academy of Ophthalmology Published by Elsevier Inc.